Kundudo feral horse: Trends, status and threats and implication for conservation - Abdurazak Sufiyan (Global Journal of Zoology - Peertechz Publications, 2022)
Kundudo feral horses are the only feral horse in Ethiopia and are located Kundudo Mountain in the eastern part of Ethiopia. The purpose of this short communication report was to compile data from different sources including secondary data, reports from the woreda focal office, and interviews with woreda experts and guards directly working on Kundudo feral horses. Data such as trends, status, and threats to Kundudo feral Horses were compiled from mentioned sources. Currently, the Kundudo feral horses were conserved in situ at the top of Kundudo Mountain. currently, in 2021 and 2022 there are a total of 30 feral horses on the top of the mountain protected by guards and the number of this horse breed will be expected to rise if protected well. The main threat Kundudo feral horses face is a logistic problem, inbreeding, low conservation activities, and animal encroachment for feeding. The major activities performed for better conservation of Kundudo feral horses are awareness-raising campaigns, Kundudo Mountain was recognized as an in-situ site by the community, and the horses moved to their original place on the mountain, personnel was hired and a management plan was developed for stakeholders. Furthermore, having many negotiations among stakeholders, prominent stakeholders have reached a consensus and signed MoU on further engagement and tried to develop a new way of communication and management arrangement. Generally, the conservation of biological diversity is important particularly the conservation of threatened animal genetic resources like the unique horse species of Kundudo Mountain because there is no duplicate copy of species that has been conserved.